2017
DOI: 10.1038/cddis.2017.305
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-dependent regulation of Cdc42 by XIAP

Abstract: Rho GTPases control fundamental cellular processes and Cdc42 is a well-studied member of the family that controls filopodia formation and cell migration. Although the regulation of Cdc42 activity by nucleotide binding is well documented, the mechanisms driving its proteostasis are not clear. Here, we demonstrate that the highly conserved, RING domain containing E3 ubiquitin ligase XIAP controls the protein stability of Cdc42. XIAP binds to Cdc42 and directly conjugates poly ubiquitin chains to the Lysine 166 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 25 publications
(26 reference statements)
2
36
1
Order By: Relevance
“…The effect of AKT-induced phosphorylation of Cdc42 on the interaction between FBXL19 and Cdc42 will be the focus of future research. Consistent with results from Murali et al (31), we also show that up-regulation of Cdc42 degradation reduces filopodia formation and tumor cell adhesion. RhoA, Cdc42, Rac1, and Rac3 belong to the Rho GTPase family and are the targets for FBXL19.…”
Section: Maintenance Of Protein Homeostasis Plays a Major Role In Thesupporting
confidence: 93%
See 1 more Smart Citation
“…The effect of AKT-induced phosphorylation of Cdc42 on the interaction between FBXL19 and Cdc42 will be the focus of future research. Consistent with results from Murali et al (31), we also show that up-regulation of Cdc42 degradation reduces filopodia formation and tumor cell adhesion. RhoA, Cdc42, Rac1, and Rac3 belong to the Rho GTPase family and are the targets for FBXL19.…”
Section: Maintenance Of Protein Homeostasis Plays a Major Role In Thesupporting
confidence: 93%
“…Cdc42 is known to be polyubiquitinated (30). A recent study from Murali et al (31) shows that ubiquitin E3 ligase XIAP targets Cdc42 for its polyubiquitination and proteasomal degradation. In the current study, we reveal that another ubiquitin E3 ligase, SCF FBXL19, regulates Cdc42 stability.…”
Section: Maintenance Of Protein Homeostasis Plays a Major Role In Thementioning
confidence: 99%
“…In this study, glutathione S-transferase (GST) conjugated OGT were used for a pull-down assay and a subsequent mass spectrometry (MS) analysis to identify the proteins that interact with OGT in HCT116 cells ( Supplementary Table S1). Among the proteins that interact with OGT, XIAP was studied because it plays an important role in tumorigenicity [7][8][9][10][11][12][13] . The pulled-down GST-OGT was immunoblotted with anti-XIAP antibody to confirm the interaction between GST-OGT and endogenous XIAP.…”
Section: Ogt Interaction With Xiapmentioning
confidence: 99%
“…XIAP plays a role in the cancer cells' resistance to anticancer drugs and studies on the antiapoptotic function of XIAP in cancer cells have been focused on depleting XIAP 6 . XIAP has many other roles besides inhibiting cancer cell death, so its involvement in cancer cell biology should be explored further [7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…XIAP has been found to be a ubiquitin E3 ligase for Mdm2 to promote its degradation (25). It is reported that the XIAP RING domain controls the protein stability of Cdc42 through directly conjugating polyubiquitin chains to the lysine 166 of Cdc42 (26). XIAP could also ubiquitinate a highly conserved Lys residue in adenylyl cyclase isoforms and thereby accelerate their endocytosis and degradation (27).…”
Section: Discussionmentioning
confidence: 99%